Association of Preoperative and Postoperative Serum Carcinoembryonic Antigen and Colon Cancer Outcome - Konishi, Tsuyoshi (JAMA Oncol, 2017)
IMPORTANCE: Guidelines recommend measuring preoperative carcinoembryonic antigen (CEA) in patients with colon cancer. Although persistently elevated CEA after surgery has been associated with increased risk for metastatic disease, prognostic significance of elevated preoperative CEA that normalized after resection is unknown. OBJECTIVE: To investigate whether patients with elevated preoperative CEA that normalizes after colon cancer resection have a higher risk of recurrence than patients with normal preoperative CEA. DESIGN, SETTING, AND PARTICIPANTS: This retrospective cohort analysis was conducted at a comprehensive cancer center. Consecutive patients with colon cancer who underwent curative resection for stage I to III colon adenocarcinoma at the center from January 2007 to December 2014 were identified. EXPOSURES: Patients were grouped into 3 cohorts: normal preoperative CEA, elevated preoperative but normalized postoperative CEA, and elevated preoperative and postoperative CEA. MAIN OUTCOMES AND MEASURES: Three-year recurrence-free survival (RFS) and hazard function curves over time were analyzed. RESULTS: A total of 1027 patients (461 [50.4%] male; median [IQR] age, 64 [53-75] years) were identified. Patients with normal preoperative CEA had 7.4% higher 3-year RFS (n = 715 [89.7%]) than the combined cohorts with elevated preoperative CEA (n = 312 [82.3%]) (P = .01) but had RFS similar to that of patients with normalized postoperative CEA (n = 142 [87.9%]) (P = .86). Patients with elevated postoperative CEA had 14.9% lower RFS (n = 57 [74.5%]) than the combined cohorts with normal postoperative CEA (n = 857 [89.4%]) (P = .001). The hazard function of recurrence for elevated postoperative CEA peaked earlier than for the other cohorts. Multivariate analyses confirmed that elevated postoperative CEA (hazard ratio [HR], 2.0; 95% CI, 1.1-3.5), but not normalized postoperative CEA (HR, 0.77; 95% CI, 0.45-1.30), was independently associated with shorter RFS. CONCLUSIONS AND RELEVANCE: Elevated preoperative CEA that normalizes after resection is not an indicator of poor prognosis. Routine measurement of postoperative, rather than preoperative, CEA is warranted. Patients with elevated postoperative CEA are at increased risk for recurrence, especially within the first 12 months after surgery.